2022
DOI: 10.3390/w14030468
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Active, Beautiful, Clean Waters Design Features in Tropical Urban Cities: A Case Study in Singapore

Abstract: In Singapore, active, beautiful, clean waters design features (ABCWDFs), such as rain gardens and vegetated swales, are used as a sustainable approach for stormwater management. Field monitoring studies characterising the performance of these design features in the tropical region are currently limited, hampering the widespread implementation of these systems. This study characterised the performance of individual ABCWDFs in the tropical climate context by monitoring a rain garden (FB7) and a vegetated swale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Regulation Services: Water Quality Af. The event mean concentrations of total suspended solids, total phosphorous, and total nitrogen are lower in catchments with green swales than without SUDS [54].…”
Section: Regulation Services: Biodiversitymentioning
confidence: 82%
See 2 more Smart Citations
“…Regulation Services: Water Quality Af. The event mean concentrations of total suspended solids, total phosphorous, and total nitrogen are lower in catchments with green swales than without SUDS [54].…”
Section: Regulation Services: Biodiversitymentioning
confidence: 82%
“…Af. The discharge quality of the catchments with bioretention ponds is better than those without them [54].…”
Section: Regulation Services: Water Qualitymentioning
confidence: 89%
See 1 more Smart Citation
“…In the momentum equation, is the bed slope, is the friction slope. is estimated using Darcy-Weisbach equation as follows, IOP Publishing doi:10.1088/1755-1315/1238/1/012022 3 (3) is estimated based on whether the flow is laminar, transitional or turbulent [10]. Equation ( 1) and ( 2) are the full dynamic wave equations, with the inclusion of inertial term.…”
Section: Surface Flow Modelmentioning
confidence: 99%
“…In Best Management Practice (BMP), swales are recommended as replacement for concrete drain. Research have shown that swales are not only efficient in managing stormwater runoff [1,2,3], but also enhance the aesthetic of the surrounding environment. Swale system is also recommended as one of solution for sustainable urban drainage system [1].…”
Section: Introductionmentioning
confidence: 99%